C03 Longitudinal Analysis Of The Behavioural Phenotype In The Zq175 (c57bl/6j) Huntington's Disease Mouse Line. (17th September 2014) - Harrison, D; Patel, Y; Tear, A; Jones, L; Dunnett, SB; Brooks, SP
Abstract : Background: Huntington's disease (HD) is a genetic disorder caused by a mutation of the huntingtin gene (HTT) resulting in an expanded polyglutamine (CAG) repeat length in the mutant huntingtin protein (mHTT). The mutation induces a progressive dysfunction of medium spiny neurones in the caudate nucleus and extensive neurodegeneration throughout the brain, causing an array of motor, cognitive and behavioural deficits. There is currently no cure and treatments are ineffective. Transgenic rodent models can provide a method of recapitulating aspects of HD, informing on underlying aberrant systems and enabling the investigation of potential intervention therapies. Aims: The present study characterises the longitudinal behavioural phenotype of the heterozygous zQ175 knock-in mouse model to evaluate the nature, severity and progression of motor and cognitive deficits in this line. Methods: zQ175 mice carrying ˜190 CAG repeats and their wildtype (Wt) littermates were tested from 3 months of age using an extensive battery of operant and non-operant behavioural tests. Results: We found that the bodyweight of Wt but not zQ175 mice increased with age up to 60 weeks. Motor performance was impaired in zQ175s on rotarod and balance beam from ˜48 weeks of age compared to Wts, with female zQ175 mice being less impaired than males on the tasks. Some differences were lost when weight was taken into account as a factor, highlighting the influence of bodyweight on certain motor tests. 24hr locomotor activity levels in both genotypes decreased with age, however zQ175 mice were less active than their Wt littermates up to 24 weeks. Inhibition of startle response was impaired in zQ175 compared to Wt from ˜36 weeks. zQ175 mice performed worse in the progressive ratio, 5-choice and serial implicit learning task tasks than the Wt group, but were no different in open field movement from 23 weeks, indicating an early decline in motivation, attention and accuracy of spatial responses. We found no difference between genotypes in classical conditioning learning at ˜16 weeks of age, nor sucrose eating (as a measure of reward value) up to 48 weeks. Conclusions: The data demonstrates that the zQ175 has a phenotype encompassing cognitive deficits from an early age with motor deficits following from ˜48 weeks, providing a HD model well suited to targeted therapeutic trials. Support: CHDI.